3D technologies in STEAM education - Ivaylo Staribratov; Nikol Manolova (Springer, 2024)
Abstract The article presents the application of 3D technologies in STEAM education through a conducted scientific research, highlighting the role of 3D modeling and 3D printing as an innovative approach in achieving an interdisciplinary learning model. The research included the following stages: preparation for designing a detailed 3D steam locomotive model; analysis of process difficulties; giving students and lecturers the opportunity to perform a specific modeling task, using basic primitives from solid geometry, as well as a questionnaire to analyze and evaluate the skills and knowledge of the participants in the 3D modeling field. In this context, the preparation process of a 3D steam locomotive model for educational purposes, using Autodesk 3ds Max software, is presented, and the 3D printing technology FDM is examined. We issued a challenge to the participants in the research to design a non-complex 3D model, using unfamiliar 3D modeling software Blender, within a limited time. The questionnaire covered topics in education, science, art, STEAM, and 3D modeling. The goal is to showcase the role of the integration of 3D technologies in educational environments with the idea of developing key skills and knowledge in learners.